Strategies in Reading English Web-Novels on Wattpad - Nur Wulandari, Ismi; Apriliaswati, Rahayu; Sri Rezeki, Yanti (ETERNAL (English Teaching Journal), 2024)
Motivated by the popularity of online reading on Wattpad, this research was conducted to investigate the metacognitive awareness of digital and online reading strategies to 39 undergraduate students who read English Web-novels on Wattpad. Additionally, the researcher explored the potential influence of English proficiency (TOEFL) and field of study, as well as the specific features of Wattpad that aid in their reading experience. Employing a quantitative survey and adapting the Metacognitive Awareness of Reading Study Inventory (MARSI) developed by Mokhtari et al. (2018). The findings indicated that participants had a moderate level of strategies when reading English web-novels on Wattpad (M = 3.42). Problem Solving Reading Strategies were the most used (M = 3.80), followed by Global Reading Strategies (M = 3.73) and Support Reading Strategies (M = 2.73). English proficiency and field of study did not significantly impactful, with all groups showing similar levels (M = 3.4). Additionally, interactive features were not considered helpful (M = 2.51 and M = 2.23, respectively), while description and figure attachment features were frequently used (M = 4.15 and M = 3.25, respectively). The results indicated a necessity to integrate specific strategies, like incorporating Global Reading Strategies for pre-reading tasks and utilizing Problem Solving Strategies during reading activities, within EFL instruction. The research highlighted the obstacles encountered by both learners and instructors in the process of teaching and acquiring reading skills. It suggested that incorporating these strategies could effectively tackle comprehension challenges and improve overall language proficiency